History and Cultural Heritage in Virtual Environments - Champion, Erik (Oxford University Press, 2014)
Applying virtual reality and virtual-world technology to historical knowledge and to cultural heritage content is generally called virtual heritage, but it has so far eluded clear and useful definitions, and it has been even more difficult to evaluate. This chapter examines past case studies of virtual heritage; definitions and classifications of virtual environments and virtual worlds; the problem of convincing, educational, and appropriate realism; how interaction is best employed; the question of ownership; and issues in evaluation. Given the premise that virtual heritage has as its overall aim to educate and engage the general public (on the culture value of the original site, cultural artifacts, oral traditions, and artworks), the conclusion suggests six objectives to keep in mind when designing virtual worlds for history and heritage.